Documentation of the Sparidae fish species in the Syrian marine waters - سعد أديب; صابور وعد; مصري مي (Latakia University Journal -Biological Sciences Series, 2021)
This research was conducted from November 2018 to December 2020, to survey the Sparidae fish species in the Syrian marine waters. Fish samples were collected from catch landing ports along the Syrian coast (Raas Al-Bassit, Lattakia, Jableh, and Tartus), which were fished by fishermen within the Syrian territorial waters exclusively, using different fishing methods (Traps, gill nets, trammel net, trawl, long line,fishing rod, spearfishing ..) The samples were transferred to the laboratory of Marine Sciences and Fish Lab, Faculty of Agriculture at Tishreen University, to take morphometric measurements and meristic data. All species have been classified, briefly described and documented. The results showed that 25 fish species belonging to 11 genera were found, in which two immigrants fish species was recorded for the first time in the Syrian marine waters, Pagellus bogaraveo as an immigrant species from the Atlantic Ocean and Pagrus major indo-pacefic species, introducd to the Eastern Basin of Mediterranean Sea. Additionnaly 5 species recorded previously in the Syrian marine waters were not found in this study.